2015
DOI: 10.1016/j.pharep.2014.10.016
|View full text |Cite
|
Sign up to set email alerts
|

Matrine suppresses proliferation and induces apoptosis in human cholangiocarcinoma cells through suppression of JAK2/STAT3 signaling

Abstract: Matrine can trigger mitochondrial apoptotic death of cholangiocarcinoma cells largely through inhibition of JAK2/STAT3 signaling. Therefore, matrine represents a potentially effective anticancer agent for cholangiocarcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“…Previous studies have shown that matrine may be used as one type of antitumor drug for leukemia and lung, liver, gastric, breast and cervical cancers, as well as numerous other types of malignant tumors with high drug resistant activity (14,15). The present study confirmed that certain concentrations of matrine could significantly inhibit the proliferation and invasion of the human hepatocellular carcinoma (HCC) cell line (16,17). However, to the best of our knowledge, the effect and mechanism of matrine on hepatic cancer stem cells in vitro has not yet been reported.…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Previous studies have shown that matrine may be used as one type of antitumor drug for leukemia and lung, liver, gastric, breast and cervical cancers, as well as numerous other types of malignant tumors with high drug resistant activity (14,15). The present study confirmed that certain concentrations of matrine could significantly inhibit the proliferation and invasion of the human hepatocellular carcinoma (HCC) cell line (16,17). However, to the best of our knowledge, the effect and mechanism of matrine on hepatic cancer stem cells in vitro has not yet been reported.…”
Section: Introductionsupporting
confidence: 80%
“…Previous studies have suggested that matrine may eliminate tumor cells by apoptosis induction (20,21). Ma et al (22) demonstrated that matrine significantly inhibited the invasion of human pancreatic cancer cells by downregulating the expression of membrane type 1-matrix metalloproteinase.…”
Section: Discussionmentioning
confidence: 99%
“…Matrine, a traditional Chinese medicine, is an alkaloid isolated from plants in the genus Sophora , comprised of four rings of quinolizidine classes (C 15 H 24 N 2 O). Matrine exhibits different biological properties, including anti-inflammatory (16), antitumor (17), anti-viral (18), anti-fibrosis (19), anti-arrhythmia (20), anti-asthmatic (21) and immunosuppressive activity (22). However, the effects of matrine on the proliferation and apoptosis of FLS have yet to be reported.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that the formulation has physiological functions, such as improving gastrointestinal function, strengthening the immune system, and speeding up the production of red blood cells (29). This formulation can also be used for the treatment of malignant tumors (9). However, in the context of evidence-based medicine, the determination of efficacy requires critical evaluation using modern medical research approaches.…”
Section: Discussionmentioning
confidence: 99%
“…Indigo jade red is used in the treatment of chronic myelogenous leukemia and can significantly inhibit tumor growth (4,5). Matrine is able to inhibit the growth of a variety of solid tumors, and has exhibited activity against pancreatic cancer, breast cancer, lung cancer and bile duct cancer cells (6)(7)(8)(9). In recent years, increasing numbers of Chinese herbal medicines or prescriptions have gained international recognition and acceptance for their anticancer effects (10).…”
Section: Introductionmentioning
confidence: 99%